Primary choroidal lymphoma with extrascleral extension and bone marrow involvement: a case report - Zhao, Lu; Li, Yingyu; Zhang, Pei; Wang, Changguan; Li, Chunyuan; Chen, Huijin (Frontiers in Medicine, 2025)
Primary extranodal marginal zone B-cell lymphoma (EMZL) of the choroid is a rare condition with a handful of cases reported in the literature. Here, we report a challenging case of primary EMZL of the choroid with extrascleral extension and bone marrow involvement. An 86-year-old male presented with 2 years of progressive vision loss in his left eye. Fundus examination revealed yellow-white subretinal infiltrates at the posterior pole. Ultrasonography detected diffuse choroidal thickening with retrobulbar hypoechoic mass. One year later, an inferior exudative retinal detachment developed. Ultrasonography revealed enlargement of the choroidal low-reflective mass. Another half a year later, visual acuity of the left eye deteriorated to no light perception (NLP) and neovascular glaucoma with intractable pain necessitated enucleation; therefore, enucleation was performed. Histopathological and immunohistochemistry findings confirmed EMZL infiltrates in the choroid and extrascleral tissue, without optic nerve involvement. Concurrent hematologic evaluation revealed significant anemia. The patient was transferred to the hematology department. Bone marrow biopsy demonstrated EMZL involvement morphologically and immunophenotypically identical to the choroidal tumor. Positron emission tomography-computed tomography (PET-CT) revealed no evidence of metabolically active lesions in the lymph nodes, spleen, or visceral organs to suggest an alternate primary tumor. Thus, a diagnosis of primary choroidal EMZL with extrascleral extension and bone marrow involvement was established. To our knowledge, this represents the first reported case of primary choroidal EMZL with bone marrow involvement.